Experimental investigation of the fireextinguishing system with a gasdetonation charge for fluid acceleration - Korytchenko, Kostyantyn; Sakun, Oleksandr; Dubinin, Dmytro; Khilko, Yurij; Slepuzhnikov, Evgen; Nikorchuk, Andriy; Tsebriuk, Ivan (Eastern-European Journal of Enterprise Technologies, 2018)
To improve the parameters of pulsed fire-extinguishing plants for long-range and mass and dimensional indicators, it was proposed to replace the pneumatic propellant charge with the gas-detonation charge. The charge is formed based on the technical propane-butane mixture with oxygen, and detonation combustion of the mixture was achieved through the application of the electric discharge system of detonation initiation. It was experimentally proved that the use of the gas-detonation charge instead of the pneumatic charge in pulsed fire-extinguishing plants makes it possible to improve their parameters. An increase in long-range of a water jet, which was achieved in the developed plant, decreases the impact of heat radiation on a rescuer, which ensures the feasibility of application of such systems for fighting large-scale fires. A decrease in gas pressure in cylinders due to transition from compression energy to chemical combustion energy ensures a decrease in the equipment weight and an increase in the number of shots with the extinguishing agent with the same dimensions of similar plants with the pneumatic charge. Specifically, in the plant with the gas-detonation charge, effective fire extinguishing distance, depending on the initial pressure of the charge within 0.1÷0.3 MPa was from 8 to 19 meters for the mass of the extinguishing agent of 1 kg and from 5 to 14 meters for the mass of the extinguishing agent of 2 kg. The parameters of the electric discharge system, which ensure detonation initiation with minimal electricity consumption, were determined. Specifically, in the case of the use of a special spark plug by two synchronized spark discharges, at complete energy of the charge of 15 J and application of the capacitor of 1.75 µF and inductivity of the discharge curciut of 400 nH, detonation occurs in the pipe of the diameter of 73 mm under conditions of the conducted research at the distance of not more than 180 mm. The obtained results could be used in designing the plants with a gas-detonation charge.